Jurisprudence Rulings Deduced from the Hadith of (Al-Nawa’) and its Contemporary Applications (Islamic Sciences Journal, 2023)
ABSTRACT                                 This research deals with the jurisprudential statement of the hadith Qudsi, the hadith of the Prophet, which is the saying of the polytheists at the time of the pre-Islamic period, our rain: (Ban such-and-such ... and such ...). This research came to separate the jurisprudential rulings related to this hadith, and it appears that the influence of the planets, celestial bodies and stars is one of the pre-Islamic customs that Islam came to contradict and fight it, for there is no influence in the universe except Allah, and that the absolute unseen is known only to the Creator, Owner, Master and Controller of the universe, Glory be to Him. Contemporary astrology and what is permissible and what is forbidden and forbidden.